Acute changes of Achilles tendon thickness investigated by ultrasonography after shotokan and kyokushin karate training - Zarzycki, A.; Stawarz, M.; Maillette, J.; Lovecchio, N.; Zago, M.; Kawczynski, A.; Klich, S. (Archives of Budo, 2018)
Background and Study Aim: Ultrasonography proved to be a useful tool to investigate the morphology of the Achilles tendon. Studies exist assessing the role of exercise on Achilles tendon morphology after vertical jump and treadmill running, and Achilles tendon dimensions noticeably decreased following heavy resistance exercise. However, little is known regarding the influence of different karate disciplines as shotokan and kyokushin on Achilles tendon thickness. Thus, this study aimed to establish whether the acute changes of Achilles tendon are a phenomenon characteristic of different styles of karate training.